2010
DOI: 10.1177/0891242410376237
|View full text |Cite
|
Sign up to set email alerts
|

Business Incentive Use Among U.S. Local Governments: A Story of Accountability and Policy Learning

Abstract: Use of business incentives is one of the most common local economic development strategies. The authors analyze national surveys of 700 to 1,000 local governments from 1994, 1999, and 2004 to track use of business incentives over time. They find a shift from primary reliance on business incentives to use of a broader set of strategies that includes business retention and small business support. The authors also find evidence of policy learning with increased attention to accountability among governments that u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(23 citation statements)
references
References 46 publications
1
21
0
1
Order By: Relevance
“…Nevertheless, regarding interlocal EDC, extant literature indicates that business attraction or retention is the most common goal of local governments (Bradshaw & Blakely, 1999;Christopherson & Clark, 2007;Olberding, 2002;Peterson, 1981;Stokan, 2013). The new business investment enhances the local government's property tax base and results in lower unemployment, the inflow of new residents, increased income, and local economic diversification (Blakely & Bradshaw, 2002;Zheng & Warner, 2010). Each city government competes against one another by diversifying and increasing subsidies and tax exemptions to attract more businesses as well as to capture the tax benefits from diverse industries by locating them in their jurisdiction (Zheng & Warner, 2010).…”
Section: Interlocal Economic Development Competition Through the Lens...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, regarding interlocal EDC, extant literature indicates that business attraction or retention is the most common goal of local governments (Bradshaw & Blakely, 1999;Christopherson & Clark, 2007;Olberding, 2002;Peterson, 1981;Stokan, 2013). The new business investment enhances the local government's property tax base and results in lower unemployment, the inflow of new residents, increased income, and local economic diversification (Blakely & Bradshaw, 2002;Zheng & Warner, 2010). Each city government competes against one another by diversifying and increasing subsidies and tax exemptions to attract more businesses as well as to capture the tax benefits from diverse industries by locating them in their jurisdiction (Zheng & Warner, 2010).…”
Section: Interlocal Economic Development Competition Through the Lens...mentioning
confidence: 99%
“…The new business investment enhances the local government's property tax base and results in lower unemployment, the inflow of new residents, increased income, and local economic diversification (Blakely & Bradshaw, 2002; Zheng & Warner, 2010). Each city government competes against one another by diversifying and increasing subsidies and tax exemptions to attract more businesses as well as to capture the tax benefits from diverse industries by locating them in their jurisdiction (Zheng & Warner, 2010).…”
Section: Interlocal Economic Development Competition Through the Lens...mentioning
confidence: 99%
“…Few empirical studies have measured changes in economic development policy over time, with some notable exceptions that focus primarily on tax incentives. Using data from the International City Management Association (ICMA) survey of public managers, Zheng and Warner (2010) found that incentive use demonstrates temporal variation: the share of local governments reporting incentive use was 88% in 1994, dipped to 55% in 2004, and then increased to 90% in 2009. In 2009, the most commonly used incentives were infrastructure improvements, tax increment financing (TIF), and tax abatements.…”
Section: Research Design and Case Selectionmentioning
confidence: 99%
“…Most municipalities used abatements modestly with the exception of a handful of larger cities that were more reliant on them. Contradicting Zheng and Warner (2010), the Michigan study implies that incentives were less popular during periods of slow growth—perhaps because fewer businesses were growing, relocating, or requesting abatements during tough times.…”
Section: Research Design and Case Selectionmentioning
confidence: 99%
“…If local governments do not undertake complex risk mitigation strategies, due to lack of aptitude and smaller municipalities, they can enter a vicious downward spiral where weak economic and fiscal development on a small footing limits fiscal capacity and the ability to adopt innovative policies (WARNER; PRATT, 2005;ZHENG;WARNER, 2010). As a result, sustainability policies are more likely to occur in cities with better fiscal health (LUBELL; FEIOCK; HANDY, 2009; SHARP; DALEY; LYNCH 2011; ZART et al, 2008).…”
Section: Governancementioning
confidence: 99%